(untitled) (REMUNOM, 2026)
Transition Metal Dichalcogenides (TMDs) are two-dimensional materials with a typical stoichiometry of XY₂, where X represents a transition metal and Y a chalcogen. This group is of significant interest to the scientific community because its constituent materials possess a monolayer analogous to graphene. Such similarity has focused research on the physical properties of these materials in search of TMDs with characteristics comparable to graphene. Unlike graphene, which has a zero bandgap, TMDs exhibit an intermediate bandgap, classifying them as semiconductors. Consequently, they are ideal candidates for integration into various sectors, particularly in the optoelectronic industry. In this context, the present study aims to elucidate certain physical properties of the monolayer of the TMD alloy CrMoS₄, a material that has not been explored in either theoretical or experimental literature. The results for the CrMoS₄ alloy can be compared to those of the monolayers of 2H–CrS₂ and 2H–MoS₂, which are well-documented in the literature. The research methodology involved the computational design of the primitive cells of 2H–CrS₂, 2H–MoS₂, and the TMD alloy CrMoS₄. Following the design phase, computational calculations of the optoelectronic properties were performed on the primitive cells in their ground state using Material Studio’s CASTEP module under the Generalized Gradient Approximation (GGA) within Density Functional Theory (DFT). The results indicate that both monolayers exhibit a bandgap ranging from 0.90 eV to 1.20 eV, and the conclusions suggest that the materials under study are both structurally stable and semiconductors.